Feasibility Analysis of Applying Appropriate Technology and Business Processes in the Small and Medium Coffee Industry - Ahmad Zamheri; Hendradinata Hendradinata; Rian Rahmanda Putra; Jovan Febriantoko (STKIP Singkawang, 2023)
This study was conducted to see the feasibility of the coffee industry through the application of appropriate technology and business processes. The research method used was descriptive quantitative. Data collection was done through observation, documentation, and a literature study. The data analysis technique used was data reduction, data presentation, and data interpretation. The results showed that the availability of raw material in the form of coffee yields had an increasing trend both nationally and in South Sumatra. In addition, the area of coffee plantations also tended to increase. The type of coffee product from South Sumatra with the highest possible commercialization opportunity was Robusta coffee. Several types of coffee products from home industries in various Regencies/Cities in South Sumatra had excellent taste and aroma so they had commercialization opportunities. The coffee industry in South Sumatra, especially in Pagaralam City was feasible to be built based on abundant raw materials and financial analysis. Raw materials from local farmers had relatively stable production and tended to increase. Suggestions and recommendations can be given to the Regional Government and the community to pay attention and intensively foster the process of cultivating wild civet coffee (Paradoxurus hermaphrodites) from various Regencies/Cities in South Sumatra by the Regional Government to have competitive commercialization opportunities.